The Influence of Teacher’s Performance and School Environment on the Implementation of Curriculum Merdeka - Meiliza Hastuti; Bukman Lian; Muhammad Fahmi (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2026)
This study aims to examine the influence of teacher performance and school environment on the implementation of the Curriculum Merdeka at SMA Negeri 5 Palembang. A quantitative approach with a survey method was employed. The sample consisted of 68 teachers selected purposively. Data were collected through questionnaires and analyzed using multiple linear regression. Findings revealed that: (1) teacher performance significantly influences Curriculum Merdeka implementation (p = 0.000 < 0.05) with a coefficient of determination (R²) of 0.646; (2) school environment significantly influences curriculum implementation (p = 0.000 < 0.05) with R² of 0.586; and (3) simultaneously, both variables significantly affect implementation (p = 0.000 < 0.05) with R² of 0.723, indicating that 72.3% of the variance in curriculum implementation is explained by teacher performance and school environment together. The research provides early empirical validation of key determinants specifically influencing the rollout of Indonesia's new Curriculum Merdeka policy, examining both human and contextual factors within a localized school setting. Schools should prioritize continuous teacher professional development and cultivate supportive physical and psychosocial environments to ensure effective curriculum implementation aligned with policy objectives. The study contributes evidence-based insights to educational policy discourse, demonstrating that successful curriculum reform requires simultaneous investment in teacher quality and conducive institutional conditions.